Preparation method of tubular ceramic carrier-based C-ZIF-67 derived nano-porous carbon doped PDMS mixed matrix membrane and application of tubular ceramic carrier-based C-ZIF-67 derived nano-porous carbon doped PDMS mixed matrix membrane in recovery of ethanol by pervaporation

By incorporating C-ZIF-67-derived nanoporous carbon particles based on tube ceramic carriers into the PDMS membrane, the problem of ZIF-67 particle agglomeration and poor interfacial compatibility is solved, and the permeability of low-concentration ethanol aqueous solution is significantly improved. Separate performance and maintain stability for long-term operation.

CN119455695AActive Publication Date: 2025-02-18JILIN INST OF CHEM TECH

Patent Information

Application Number
CN202411518305.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-18
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

The existing PDMS membrane and ZIF-67/PDMS mixed matrix membrane are insufficient in the separation performance of low-concentration ethanol aqueous solution, the ZIF-67 particles are severely agglomerated, the interface compatibility is not ideal, and the stability is reduced.

Method used

The preparation method of using C-ZIF-67 derived nanoporous carbon based on tube ceramic support is incorporated into PDMS mixed matrix membrane, and C-ZIF-67 filler particles are prepared by high-temperature calcination to improve the dispersion of particles in the membrane and the dispersion with PDMS. Compatibility.

Benefits of technology

The permeability and vaporization separation performance of ethanol/aqueous solution is significantly improved, and the separation factor and total flux are maintained stable, with excellent long-term operation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455695A_ABST
    Figure CN119455695A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of ethanol recovery, and relates to a preparation method of a tubular ceramic carrier-based C-ZIF-67 derived nano-porous carbon doped PDMS mixed matrix membrane and an application of the membrane in recovery of ethanol by pervaporation of a low-concentration ethanol aqueous solution. Comprising the following steps: synthesizing a ZIF-67 crystal, and carbonizing the ZIF-67 crystal to obtain C-ZIF-67 filler particles; the ZIF-67-derived nano-porous carbon particles are prepared through a high-temperature calcination method, the particles are fully carbonized at a certain calcination temperature, disappearance of characteristic groups after carbonization can reduce the influence of surface electrical properties of the particles, and the size shrinkage of the particles is reduced, so that the dispersity of the particles in a matrix membrane is improved; meanwhile, the MOF skeleton structure is still reserved after carbonization, the pore diameter is increased, the carbon material also has strong hydrophobicity, the hydrophobic large-pore-diameter separation pore channels are more beneficial to passing of ethanol molecules and promotion of the separation effect, the separation factor and the total flux are almost kept unchanged after long-time operation and use, and excellent performance is shown; good application prospects are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ethanol recovery, and relates to a mixed matrix membrane for recovering ethanol by pervaporation and a preparation method thereof, and in particular to a preparation method of a C-ZIF-67-derived nanoporous carbon-doped PDMS mixed matrix membrane based on a tubular ceramic carrier and an application thereof in recovering ethanol by pervaporation of a low-concentration ethanol aqueous solution. Background Art

[0002] The world's over-reliance on fossil fuels has caused serious energy crises and environmental problems. Renewable biomass has attracted much attention as an alternative resource. Bioethanol, as a valuable biofuel, has great market potential, but its current fermentation, production and separation technologies face challenges, such as end-product inhibition and high-energy-consuming distillation processes.

[0003] Pervaporation is a promising membrane separation technology with the advantages of simple operation, low energy consumption, high efficiency and non-toxicity. Polydimethylsiloxane (PDMS) membranes have been widely studied due to their strong hydrophobicity, good permeability and stability, and low cost, but the ethanol separation performance of traditional PDMS membranes is insufficient, which limits their large-scale application.

[0004] Adding fillers to PDMS to prepare mixed matrix membranes (MMMs) can improve membrane performance. Metal organic frameworks (MOFs) are widely used as doped fillers in the preparation of MMMs. For example, ZIF-67 has a high specific surface area, adjustable pore size and small size structure, strong hydrophobicity, and is easy to synthesize at room temperature. It can be used as a doped filler. However, so far, a large number of studies have focused on the synthesis of MMMs using sheet carriers as supports and the pervaporation separation of ethanol and aqueous solutions, while research on the use of tubular ceramic carriers is still lacking. Tubular ceramic carriers have the advantages of strong chemical stability and high mechanical strength, and are widely used in current industrial production (industrial production uses tubular membranes).

[0005] ZIF-67 / PDMS MMM was first prepared using ceramic tubes as carriers and applied to the pervaporation separation of low-concentration ethanol aqueous solutions, but there are some shortcomings:

[0006] (1) ZIF-67 particles agglomerated severely on the tubular support, resulting in limited improvement in the separation factor;

[0007] (2) The interfacial compatibility between ZIF-67 and PDMS is not ideal, and the stability is reduced.

[0008] The present invention aims to solve the problems existing in the prior art of PDMS membrane and ZIF-67 / PDMS MMM in the separation of low-concentration ethanol aqueous solution, such as ZIF-67 particle agglomeration and unsatisfactory interface solubility, and provide a mixed matrix membrane with better performance and a preparation method thereof. Summary of the invention

[0009] In order to make up for the shortcomings of the prior art, the present invention first prepared ZIF-67 / PDMS MMM using ceramic tubes as carriers and applied it to the pervaporation separation of low-concentration ethanol aqueous solution, but there are shortcomings:

[0010] (1) ZIF-67 particles agglomerated severely on the tubular support, resulting in limited improvement in the separation factor;

[0011] (2) The interfacial compatibility between ZIF-67 and PDMS is not ideal, and the stability is reduced.

[0012] The reasons for the deficiency were further analyzed:

[0013] ZIF-67 particles themselves have the characteristic of easy agglomeration (this phenomenon is more obvious in the process of synthesizing ZIF-67 in this study), which is due to the electrical properties of the surface groups of the zeolite-imidazole salt skeleton structure. Therefore, they are severely agglomerated and have poor dispersibility in the PDMS matrix membrane; this also further affects its solubility with PDMS, resulting in some defects on the membrane surface. After long-term use, some ZIF-67 falls off, and the stability is reduced.

[0014] The solution to this case is: retain the porous skeleton structure of ZIF-67, eliminate the effect of surface groups, and at the same time not reduce its hydrophobic properties; therefore, considering the preparation of ZIF-67-derived nanoporous carbon particles by high-temperature calcination, they are fully carbonized at a certain calcination temperature. The disappearance of characteristic groups after carbonization can reduce the influence of its surface electrical properties, and the particle size shrinks and decreases, all of which help to improve its dispersion in the matrix membrane; at the same time, the MOF skeleton structure is still retained after carbonization, and the pore size becomes larger. The carbon material also has strong hydrophobicity. These hydrophobic large-pore separation channels are more conducive to the passage of ethanol molecules, thereby promoting the improvement of its separation effect.

[0015] The technical solution adopted by the present invention to solve the technical problem is: a method for preparing a C-ZIF-67-derived nanoporous carbon-doped PDMS mixed matrix membrane based on a tubular ceramic carrier, comprising the following steps:

[0016] S1: Synthesize ZIF-67 crystals, dissolve Co(NO3)2·6H2O in methanol; then dissolve Hmim in methanol; then mix the two solutions and stir them continuously at room temperature for 2 hours to obtain purple crystals, collect the obtained purple crystals by centrifugation at 8000 rpm for 10 minutes, and repeatedly wash them with methanol, and finally vacuum dry the obtained crystals at 80°C overnight to obtain ZIF-67 crystals;

[0017] S2: Preparation of C-ZIF-67 filler particles: The synthesized ZIF-67 crystals were carbonized and then collected. The collected particles were washed with methanol to remove residues and finally vacuum dried at 80°C overnight to obtain C-ZIF-67 filler particles.

[0018] S3: Treatment of α-alumina ceramic tube carrier: First, polish the ceramic tube with 800# coarse sandpaper and 1500# fine sandpaper respectively, then calcine to remove impurities, then ultrasonically clean for 5 minutes and use pure water to clean to obtain an α-alumina ceramic tube carrier. Soak the α-alumina ceramic tube carrier in pure water before use. When needed, wipe off excess water on the surface of the α-alumina ceramic tube carrier with filter paper and let it stand to dry for use.

[0019] S4: Preparation of PDMS-based mixed matrix membrane: C-ZIF-67 filler particles were added to n-heptane, and the mixture was ultrasonically treated for 1 hour after stirring. PDMS was added and stirred for 4 hours. PDMS was added to the mixed solution again and stirred for 12 hours. Then, the cross-linking agent TEOS and the catalyst DBTOL were added respectively, and the mixture was allowed to stand for degassing. The C-ZIF-67-filled PDMS solution was coated on the outer surface of the α-alumina ceramic tube support by dip coating for 1 minute, and the mixture was allowed to stand at room temperature for 24 hours. The mixture was then vacuum dried at 90°C for 12 hours to prepare a C-ZIF-67-derived nanoporous carbon-doped PDMS mixed matrix membrane based on a tubular ceramic support.

[0020] Furthermore, the Co(NO3)2·6H2O in S1 is 0.1-0.4g; the methanol is 10g-15g; and the Hmim is 0.2-0.5g.

[0021] Furthermore, the Co(NO3)2·6H2O is 0.29 g; the methanol is 11.8 g; and the Hmim is 0.33 g.

[0022] Further, the carbonization conditions of the ZIF-67 crystals in S2 are as follows: the initial temperature is room temperature, the temperature is increased in a nitrogen environment, and the heating rate is 5°C·min -1 , heat to 700℃, keep warm for 2h, and then cool down naturally.

[0023] Furthermore, 0.1-0.3 g of C-ZIF-67 filler particles, 20-30 g of n-heptane, and a total amount of PDMS of 1-3 g are used, the first addition amount is 10% of the mass of the filler particles, and the second addition amount is the remaining mass of PDMS.

[0024] Furthermore, the mass of the C-ZIF-67 filler particles is 0.2625 g, the mass of n-heptane is 25 g, and the total mass of PDMS is 1.75 g.

[0025] Furthermore, the added mass ratio of PDMS, cross-linking agent TEOS and catalyst DBTOL is 1:0.1:0.05.

[0026] The application of pervaporation to recover ethanol is characterized by: using the prepared C-ZIF-67-derived nanoporous carbon-doped PDMS mixed matrix membrane based on a tubular ceramic carrier to recover ethanol through pervaporation.

[0027] The beneficial effects of the present invention are as follows:

[0028] The present invention discloses a method for preparing a C-ZIF-67-derived nanoporous carbon-doped PDMS mixed matrix membrane based on a tubular ceramic carrier and an application of pervaporation to recover ethanol. The prepared C-ZIF-67 / PDMS MMM particles retain the original MOF skeleton structure and have a larger pore size. At the same time, the carbon component has strong hydrophobicity, relatively good dispersibility and better compatibility with PDMS. These structural and property advantages significantly improve the PV performance of C-ZIF-67 / PDMS MMM in ethanol / water solution compared with pure PDMS membrane and ZIF-67 / PDMSMMM. Moreover, the separation factor and total flux remain almost unchanged after long-term operation, showing excellent performance and having good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The present invention will be further described below in conjunction with the accompanying drawings.

[0030] Figure 1 is a flow chart of the method of the present invention;

[0031] Figure 2 Schematic diagram of a pervaporation performance testing device of the present invention;

[0032] Figure 3 The XRD patterns and TGA curves of ZIF-67 and C-ZIF-67 particles of the present invention;

[0033] Figure 4 is the infrared spectrum of ZIF-67 and C-ZIF-67 particles of the present invention;

[0034] Figure 5 is a scanning electron microscope image of ZIF-67 and C-ZIF-67 particles of the present invention;

[0035] Figure 6 are nitrogen adsorption-desorption isotherms and pore size distribution diagrams of ZIF-67 and C-ZIF-67 particles of the present invention;

[0036] Figure 7are scanning electron micrographs of the surfaces and cross-sections of pure PDMS membranes, ZIF-67 / PDMS-15wt% and C-ZIF-67 / PDMS-15wt% MMMs of the present invention;

[0037] Figure 8 is a water contact angle diagram of pure PDMS membrane, ZIF-67 / PDMS-15wt% MMM and C-ZIF-67 / PDMSMMMs with different loading amounts of the present invention;

[0038] Fig. 9 is a pervaporation performance diagram of ZIF-67 / PDMS MMMs at different ZIF-67 loadings and C-ZIF-67 / PDMS MMMs at different C-ZIF-67 loadings of the present invention;

[0039] Fig.10 It is a comparison chart of the pervaporation performance of pure PDMS membrane, ZIF-67 / PDMS-15wt% and C-ZIF-67 / PDMS-15wt% MMMs of the present invention;

[0040] Fig.11 It is a long-term pervaporation performance diagram of C-ZIF-67 / PDMS-15wt%MMM of the present invention. DETAILED DESCRIPTION

[0041] In order to make the technical means, creative features, objectives and effects of the present invention easy to understand, the following Figure 1-Figure 11 The present invention is further described in combination with specific embodiments and comparative examples.

[0042] Example:

[0043] like Figure 1 As shown, preparation of C-ZIF-67 derived nanoporous carbon incorporated into PDMS mixed matrix membrane based on tubular ceramic support:

[0044] Synthesis of ZIF-67 crystals: dissolve 0.29 g Co(NO3)2·6H2O in 11.8 g methanol; then dissolve 0.33 g Hmim in 11.8 g methanol; then mix the two solutions and stir continuously for 2 h at room temperature to obtain purple crystals, collect the product by centrifugation at 8000 rpm for 10 min, and repeatedly wash with methanol, and finally dry the obtained crystals in vacuum at 80°C overnight to obtain ZIF-67 crystals.

[0045] Carbonization of ZIF-67 crystals: The synthesized ZIF-67 crystals were heated in a nitrogen environment at an initial temperature of room temperature at a rate of 5 °C min -1, the temperature was raised to 700°C and kept for 2 hours, then naturally cooled, the carbonized particles were collected and washed with methanol to remove the residue, and finally vacuum dried at 80°C overnight to obtain C-ZIF-67 filler particles.

[0046] Treatment of α-alumina ceramic tube carrier: First, polish the ceramic tube with coarse sandpaper (800#) and fine sandpaper (1500#), respectively, then calcine to remove impurities, then ultrasonically clean for 5 minutes and use pure water to clean, then soak in pure water for 24 hours, fill the pores of the carrier with water to prevent the coating polymer solution from penetrating into the pores, and take it out 1 hour before immersing the coating polymer solution, wipe off excess water on the surface of the ceramic tube with filter paper, and let it stand to dry for use.

[0047] Preparation of PDMS-based mixed matrix membrane: 0.2625g of C-ZIF-67 filler particles were added to 25g of n-heptane, stirred and ultrasonically treated for 1h. Then a partial amount of PDMS (10% of the mass of the filler particles) was added, stirred for 4h, and the remaining amount of PDMS was added to the mixed solution, stirred for 12h, and the total mass of PDMS added was 1.75g ​​(7.0wt% PDMS concentration in n-heptane); then the crosslinker TEOS and the catalyst DBTOL (the ratio of PDMS / TEOS / DBTOL was 1 / 0.1 / 0.05) were added respectively, and the mixture was allowed to stand for degassing. The PDMS solution filled with C-ZIF-67 was coated on the outer surface of the treated α-alumina ceramic tube support by dip coating for 1min. After standing at room temperature for 24h, it was vacuum dried at 90℃ for 12h to finally prepare a C-ZIF-67 filled PDMS / ceramic tube mixed matrix membrane.

[0048] Comparative Example 1:

[0049] Preparation of ZIF-67 filled PDMS / ceramic tube mixed matrix membrane:

[0050] Synthesis of ZIF-67 crystals: dissolve 0.29 g Co(NO3)2·6H2O in 11.8 g methanol; then dissolve 0.33 g Hmim in 11.8 g methanol; then mix the two solutions and stir continuously for 2 h at room temperature to obtain purple crystals, collect the product by centrifugation at 8000 rpm for 10 min, and repeatedly wash with methanol, and finally dry the obtained crystals in vacuum at 80°C overnight to obtain ZIF-67 crystals.

[0051] Treatment of α-alumina ceramic tube carrier: First, polish the ceramic tube with coarse sandpaper (800#) and fine sandpaper (1500#), respectively, then calcine to remove impurities, then ultrasonically clean for 5 minutes and use pure water to clean, then soak in pure water for 24 hours, fill the pores of the carrier with water to prevent the coating polymer solution from penetrating into the pores, and take it out 1 hour before immersing the coating polymer solution, wipe off excess water on the surface of the ceramic tube with filter paper, and let it stand to dry for use.

[0052] Preparation of PDMS-based mixed matrix membrane: 0.2625g of CZIF-67 filler particles were added to 25g of n-heptane, and ultrasonic treatment was performed for 1h after stirring. Then a partial amount of PDMS (10% of the mass of the filler particles) was added, stirred for 4h, and the remaining amount of PDMS was added to the mixed solution, stirred for 12h, and the total mass of PDMS added was 1.75g ​​(7.0wt% PDMS concentration in n-heptane). Subsequently, crosslinking agent TEOS and catalyst DBTOL (the ratio of PDMS / TEOS / DBTOL was 1 / 0.1 / 0.05) were added respectively, and the mixture was allowed to stand for degassing. The PDMS solution filled with ZIF-67 was coated on the outer surface of the treated α-alumina ceramic tube carrier by dip coating for 1min. After standing at room temperature for 24h, it was vacuum dried at 90°C for 12h to finally prepare a ZIF-67-filled PDMS / ceramic tube mixed matrix membrane.

[0053] Comparative Example 2:

[0054] Preparation of pure PDMS membrane: 1.75 g PDMS was added to 25 g n-heptane, stirred at room temperature for 6 h, then the crosslinker TEOS and the catalyst DBTOL (the ratio of PDMS / TEOS / DBTOL was 1 / 0.1 / 0.05) were added respectively, and allowed to stand for degassing; the PDMS solution was coated on the outer surface of the pretreated tubular ceramic support by dip coating for 1 min; it was allowed to stand at room temperature for 24 h, and then vacuum dried at 90°C for 12 h to finally prepare a pure PDMS membrane.

[0055] The membranes prepared in Example 1 and Comparative Example 2 were subjected to pervaporation experiments as follows:

[0056] like Figure 2 As shown in the figure, the tubular membrane is connected to the stainless steel tube with vacuum sealant and then installed in the pervaporation device. The effective membrane area is 0.001695m 2 The feed solution is a 5 wt% ethanol aqueous solution, the temperature is controlled at 60°C, and the vacuum is evacuated by a vacuum pump, and the vacuum degree is maintained below 400 Pa.

[0057] Before collecting samples, the entire pipeline system was preheated for 2 h, and then the permeate was collected in a cold trap immersed in liquid nitrogen; after the experiment, the collected samples were weighed and analyzed by gas chromatography.

[0058] Total flux of permeate J, through-flux and partial flux J i Calculated by the following formulas:

[0059]

[0060] J i =y wi J

[0061] Where J is the total flux, in g / m 2 h; Q is the total mass of the permeate, in kg; A is the effective area of ​​the membrane, in m 2 ; t is the pervaporation collection time, in h; y wi is the mass fraction of component i in the permeate;

[0062] The membrane separation factor α is calculated by the ratio of the mass fractions of the two components on the permeate side y and the feed side x, as follows:

[0063]

[0064] Through the above experiments, the conclusions are as follows:

[0065] Characterization of ZIF-67 and C-ZIF-67 particles:

[0066] like Figure 3 As shown, the synthesized ZIF-67 particles before and after carbonization were characterized by XRD. Figure 3 The characteristic diffraction peak in (a) is consistent with the spectrum of ZIF-67 in the prior art, and no other impurities exist, indicating that ZIF-67 particles have been synthesized and the diffraction peak position points to the sodalite structure.

[0067] Figure 3 (b) is the TGA curve of ZIF-67 particles to analyze its carbonization thermal decomposition process. In the range of 100-200°C, the removal of water adsorbed in the pores causes the weight to gradually decrease; the weight loss above 200°C may be due to the escape of residual solvent from the pores or the decomposition of unreacted connectors; around 550°C is the decomposition of -CH3, and after 550-600°C is the release process of CNH, 600-700°C is its main decomposition and carbonization temperature, and 700°C achieves complete decomposition and carbonization.

[0068] like Figure 3 As shown in (c), the XRD spectrum of C-ZIF-67 is Figure 3Compared with ZIF-67 in (a), the characteristic peak disappears and it becomes amorphous. The two broad peaks at 24° and 44° are the (002) and (101) phases of graphite carbon, respectively. It is preliminarily judged that ZIF-67 has been carbonized.

[0069] like Figure 4 As shown, the chemical structures of ZIF-67 and carbonized C-ZIF-67 particles were further investigated by infrared spectroscopy; Figure 4 The absorption peak of ZIF-67 is mainly attributed to the 2-methylimidazole ligand, 600-1500 cm -1 The peaks in the range are the result of stretching and bending vibrations of the imidazole group, 1460 cm –1 A small peak at the position corresponds to the stretching mode of C=N bonding. The characteristic absorption peaks of the synthesized particles are consistent with the results in the prior art, further indicating the successful synthesis of ZIF-67. After carbonization, the absorption peaks at the corresponding positions almost completely disappeared, indicating that calcination at 700°C led to the decomposition of organic ligands and ZIF-67 was successfully carbonized. The disappearance of characteristic groups after carbonization can reduce the influence of its surface electrical properties, thereby reducing the degree of agglomeration of particles in MMM.

[0070] like Figure 5 As shown, the prepared ZIF-67 crystal morphology is highly crystalline rhombic dodecahedron particles with sharp edges, and the size is about 300nm; Figure 5 (b) SEM image of C-ZIF-67. The morphology of the corresponding particles has not changed significantly, and the regular rhombic dodecahedron shape is still retained, indicating that there is no structural damage after carbonization. In this way, its original MOF skeleton structure can be used as MMM filler for the next application. Figure 5 It can also be seen in (b) that the particle size is significantly reduced after carbonization, which also helps to improve its dispersion in MMM.

[0071] like Figure 6 As shown in (a), the nitrogen adsorption-desorption curve of ZIF-67 belongs to type I isotherm, indicating that it is a microporous material; Figure 6 (b) is the nitrogen adsorption-desorption curve after carbonization, showing a type IV isotherm with an H3 type hysteresis loop, which reflects that the carbonized particles are mostly mesoporous. Figure 6 The pore size distribution curve of (c) also illustrates this result; as shown in the following table:

[0072]

[0073] Pore ​​structure characteristics of ZIF-67 and C-ZIF-67

[0074] The pore structure characteristics are given. The total pore volume of C-ZIF-67 after carbonization increases from 0.7443 cm3 g -1 Reduced to 0.3187cm 3 g –1 , the micropore volume is from 0.7039cm 3 g -1 Reduced to 0.1693cm 3 g –1 The pore volume changes from mostly micropore volume to mostly mesopore volume; the average pore diameter increases from 2.18nm to 3.57nm, and the pore size distribution becomes wider after carbonization, and has a larger pore size. Combined with the above SEM results, it shows that the C-ZIF-67 particles still retain the original MOF skeleton structure, while the pore size is further increased compared to ZIF-67.

[0075] Characterization of membrane materials:

[0076] The SEM morphologies of PDMS membrane, ZIF-67 / PDMS-15wt% and C-ZIF-67 / PDMS-15wt% MMMs are shown in Figure 2. Figure 7 As shown; Figure 7 (a) and (b) show that the surface of the PDMS membrane is dense, smooth and defect-free, and the thickness of the membrane is about 7 μm. From the surface and cross section of ZIF-MMMs, it can be seen that Figure 7 (c), (d), (e), and (f) show that the surface of the MMMs membrane doped with ZIF-67 and C-ZIF-67 particles becomes rough, which is consistent with the result that the water contact angle of the MMMs surface increases after doping with particles. It is worth noting that there is a certain degree of particle agglomeration in the ZIF-67 / PDMS MMM, which further leads to the inability of some particles to form a good fusion with PDMS. In contrast, the C-ZIF-67 / PDMS MMM particles are less agglomerated, and C-ZIF-67 and PDMS are well soluble, reducing the defects caused by the difficulty of the viscous polymer solution to penetrate the gaps between the agglomerated particles. The cross-section shows that the average thickness of the selective membrane layer of ZIF-MMMs is about 10 μm, which is thicker than the pure PDMS membrane, and there is no obvious peeling from the support layer.

[0077] The surface hydrophobic properties of ZIF-67 / PDMS and C-ZIF-67 / PDMS MMMs with different particle loadings were evaluated by water contact angle measurements:

[0078]

[0079] Water contact angle of ZIF-67 / PDMS MMMs

[0080] from Figure 8As can be seen from the above table, the water contact angle of ZIF-67 / PDMS MMM is always higher than that of pure PDMS membrane (115°). This is because the introduction of ZIF-67 particles with a certain hydrophobicity increases the roughness of the membrane surface. Due to the inherent strong hydrophobicity of the carbonized particles and their good compatibility with PDMS, at each loading concentration, the water contact angle of C-ZIF-67 / PDMS MMM is higher than that of ZIF-67 / PDMS. In addition, as the filler loading increases from 5% to 25%, the water contact angle continues to increase, from 121° to 135°. This is because the roughness of the membrane surface increases with the increase in loading.

[0081] Comparison of membrane pervaporation performance:

[0082] The pervaporation separation performance of ethanol-water solution of ZIF-67 / PDMS and C-ZIF-67 / PDMS MMMs with different particle loadings was further studied; operating conditions: 5.0 wt% ethanol-water solution, 60 °C; Fig. 9 As shown in (a), when the ZIF-67 loading increased from 0 to 25wt%, the flux decreased from 1.62 to 0.19kg / m2·h. The main reason is that on the one hand, the tubular carrier caused the MMM to have different degrees of particle agglomeration during the preparation process (the same is true for C-ZIF-67 / PDMS MMM);

[0083] The preparation of MMM using a sheet carrier: using a scraper to scrape the mixed solution into a film with a thickness of 150μm on a sheet substrate, the particles can be dispersed more evenly and the degree of agglomeration can be greatly reduced; on the other hand, the surface groups of ZIF-67 affect its surface electrical properties, making it easy to agglomerate, resulting in poor dispersion, so the flux gradually decreases and is lower than that of pure PDMS membrane. The separation factor increases from 5.9 to 7.9 with the increase of particle loading, reaching the highest value, which is higher than that of pure PDMS membrane. Since ZIF-67 particles have a certain hydrophobicity, the hydrophobicity of the composite membrane increases, so the separation factor gradually increases; but in the range of ZIF-67 loading from 15wt% to 25wt%, the separation factor begins to decrease. This is because the excessive filler loading leads to more serious agglomeration, which causes more interface defects between ZIF-67 and PDMS. Overall, the separation factor is improved by adding ZIF-67, but due to the easy agglomeration of ZIF-67 particles themselves and the lack of good fusion with PDMS, the separation selectivity is not greatly improved, and the stability is reduced after long-term use.

[0084] Carbonized ZIF-67 particles were added into the PDMS matrix to replace ZIF-67. The pervaporation performance of C-ZIF-67 / PDMSMMM at different loading amounts was shown in Figure 2. Fig. 9As shown in (b), the separation factor increases with the increase of particle loading, and then decreases after reaching a maximum at 15wt%, with a maximum value of 9.2. Compared with ZIF-67, the separation factor of each concentration is improved; the flux also shows a gradual downward trend from 1.62 to 0.21kg / m 2 ·h, and are all lower than PDMS, but higher than ZIF-67 at each concentration; due to the inherent strong hydrophobicity of the carbon component, relatively good dispersibility and better solubility with PDMS, it has better separation selectivity than ZIF-67; at the same time, the large-pore MOF skeleton structure and reduced agglomeration further reduce the solution transmission resistance and improve the flux.

[0085] like Fig.10 As shown in the figure, the operating conditions are: 5.0wt% ethanol aqueous solution, 60℃; the pervaporation performance of pure PDMS, ZIF-67 / PDMS-15wt% and C-ZIF-67 / PDMS-15wt% for ethanol recovery is compared. It can be seen that the separation factor of C-ZIF-67 / PDMS-15wt% is the highest, reaching 9.2; in terms of total flux, MMMs are lower than pure PDMS, but C-ZIF-67 / PDMS-15wt% is higher than ZIF-67 / PDMS-15wt%, reaching 1.04kg / m 2 ·h; Overall, C-ZIF-67 / PDMS-15wt%MMM has the best pervaporation separation performance.

[0086] Stability test of C-ZIF-67 / PDMS MMM:

[0087] The long-term stability of the membrane is crucial for industrial applications. Therefore, in order to evaluate the practical application potential, the long-term stability test of C-ZIF-67 / PDMS MMM in 5.0 wt% ethanol aqueous solution at 60 °C was carried out. The results are shown in Figure 2. Fig.11 As shown, it can be clearly seen that the separation factor and total flux remained almost unchanged over a period of 60 h, with only some small fluctuations that may be caused by concentration deviations of the feed solution; although longer tests are still needed before true industrialization, the above results have preliminarily demonstrated that C-ZIF-67 / PDMS MMM has high operational stability in potential applications.

[0088] in conclusion:

[0089] In order to improve the separation performance of pure PDMS membrane and ZIF-67 / PDMS MMM in low concentration ethanol / water solution, an effective method of adding C-ZIF-67 into the PDMS matrix was proposed, and C-ZIF-67 / PDMS MMM was successfully prepared; the carbonized particles retained the original MOF skeleton structure and had larger pore size, while the carbon component had strong hydrophobicity, relatively good dispersibility and better compatibility with PDMS; these structural and property advantages made the PV performance of C-ZIF-67 / PDMS MMM significantly improved in ethanol / water solution compared with pure PDMS membrane and ZIF-67 / PDMS MMM; at 60°C, the MMM with a loading of 15wt% in 5wt% ethanol-water solution had the best PV performance with a flux of 1.04kg / m 2 ·h, and the separation factor was 9.2; finally, the stability of C-ZIF-67 / PDMSMMM was evaluated, and the separation factor and total flux remained almost unchanged after long-term operation; therefore, C-ZIF-67 / PDMS composite membrane has excellent performance and has good application prospects.

[0090] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a C-ZIF-67 derived nanoporous carbon doped with PDMS mixed matrix membrane based on a tubular ceramic support, characterized in that: The steps include: S1: Synthesize ZIF-67 crystals, dissolve Co(NO3)2·6H2O in methanol; then dissolve Hmim in methanol; then mix the two solutions and stir them continuously at room temperature for 2 hours to obtain purple crystals, collect the obtained purple crystals by centrifugation at 8000 rpm for 10 minutes, and repeatedly wash them with methanol, and finally vacuum dry the obtained crystals at 80°C overnight to obtain ZIF-67 crystals; S2: Preparation of C-ZIF-67 filler particles: The synthesized ZIF-67 crystals were carbonized and then collected. The collected particles were washed with methanol to remove residues and finally vacuum dried at 80°C overnight to obtain C-ZIF-67 filler particles. S3: Treatment of α-alumina ceramic tube carrier: First, polish the ceramic tube with 800# coarse sandpaper and 1500# fine sandpaper respectively, then calcine to remove impurities, then ultrasonically clean for 5 minutes and use pure water to clean to obtain an α-alumina ceramic tube carrier. Soak the α-alumina ceramic tube carrier in pure water before use. When needed, wipe off excess water on the surface of the α-alumina ceramic tube carrier with filter paper and let it stand to dry for use. S4: Preparation of PDMS-based mixed matrix membrane: C-ZIF-67 filler particles were added to n-heptane, and the mixture was ultrasonically treated for 1 hour after stirring. PDMS was added and stirred for 4 hours. PDMS was added to the mixed solution again and stirred for 12 hours. Then, the cross-linking agent TEOS and the catalyst DBTOL were added respectively, and the mixture was allowed to stand for degassing. The C-ZIF-67-filled PDMS solution was coated on the outer surface of the α-alumina ceramic tube support by dip coating for 1 minute, and the mixture was allowed to stand at room temperature for 24 hours. The mixture was then vacuum dried at 90°C for 12 hours to prepare a C-ZIF-67-derived nanoporous carbon-doped PDMS mixed matrix membrane based on a tubular ceramic support.

2. The method for preparing a C-ZIF-67 derived nanoporous carbon doped PDMS mixed matrix membrane based on a tubular ceramic support according to claim 1, characterized in that: The Co(NO3)2·6H2O in S1 is 0.1-0.4g; the methanol is 10g-15g; and the Hmim is 0.2-0.5g.

3. The method for preparing a C-ZIF-67 derived nanoporous carbon doped PDMS mixed matrix membrane based on a tubular ceramic support according to claim 1, characterized in that: The Co(NO3)2·6H2O is 0.29g; the methanol is 11.8g; and the Hmim is 0.33g.

4. The method for preparing a C-ZIF-67 derived nanoporous carbon doped PDMS mixed matrix membrane based on a tubular ceramic support according to claim 1, characterized in that: The carbonization conditions of ZIF-67 crystals described in S2 are as follows: the initial temperature is room temperature, the temperature is increased in a nitrogen environment, and the heating rate is 5°C·min -1 , heat to 700℃, keep warm for 2h, and then cool down naturally.

5. The method for preparing a C-ZIF-67 derived nanoporous carbon doped PDMS mixed matrix membrane based on a tubular ceramic support according to claim 1, characterized in that: 0.1-0.3 g of C-ZIF-67 filler particles, 20-30 g of n-heptane, and a total amount of PDMS of 1-3 g. The first addition amount is 10% of the mass of the filler particles, and the second addition amount is the remaining mass of PDMS.

6. The method for preparing a C-ZIF-67 derived nanoporous carbon doped PDMS mixed matrix membrane based on a tubular ceramic support according to claim 1, characterized in that: The mass of the C-ZIF-67 filler particles is 0.2625 g, the mass of n-heptane is 25 g, and the total mass of PDMS is 1.75 g.

7. The method for preparing a C-ZIF-67 derived nanoporous carbon doped PDMS mixed matrix membrane based on a tubular ceramic support according to any one of claim 5 or claim 6, characterized in that: The added mass ratio of PDMS, cross-linking agent TEOS and catalyst DBTOL is 1:0.1:0.

05.

8. Application of pervaporation to recover ethanol, characterized in that: The method for preparing a C-ZIF-67-derived nanoporous carbon-doped PDMS mixed matrix membrane based on a tubular ceramic carrier described in any one of claims 1 to 7 is used to prepare a C-ZIF-67-derived nanoporous carbon-doped PDMS mixed matrix membrane based on a tubular ceramic carrier, and ethanol is recovered by pervaporation.

Citation Information

Patent Citations

  • Porous granule MCM-41-ZIF-8 / PDMS pervaporation hybrid membrane, preparation and application

    CN103816814A

  • Preparation method of high dispersion metal-organic framework (MOF) / organic hybrid priority alcohol through composite membrane

    CN104001426A

  • Foamy carbon doped ZIF-67 pyrolysis derived carbon material and preparation method thereof

    CN111036219A

  • Graphite alkynyl alcohol permselective pervaporation membrane and preparation method thereof

    CN117582822A

  • Ethanol separation by a mixed matrix membrane

    US20090236285A1

Cited By

  • Preparation method and application of basalt fabric-based pervaporation membrane

    CN121314377A

  • ZIF-11-PDMS / GO-PI mixed matrix pervaporation membrane for ethanol recovery as well as preparation method and application of ZIF-11-PDMS / GO-PI mixed matrix pervaporation membrane

    CN121944796A